FAKTOR – FAKTOR YANG MEMENGARUHI MINAT BERINVESTASI PADA DEPOSITO SYARIAH - Pasha, Rafithoriq Aditya Pasha; Kornitasari, Yenny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research was conducted to identify the factors that influence a person’s interest in using Sharia deposits. The purpose of this research is to broaden public knowledge about Sharia deposit products, and to determine whether investment knowledge factors, risk preference factors, and income factors influence investment interest in Sharia deposit products. The research method used is descriptive analysis research with data collection through questionnaires or surveys on the productive age workforce in DKI Jakarta. The results of this study indicate that the independent variables in this study have a positive and significant effect on the interest in using Sharia deposit products. With the many investment products offered, deposits are still an option for investing and are still one of the safe investments for investors even though the returns obtained by depositors are relatively low compared to other investment products.